2021
DOI: 10.1002/adma.202103751
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Topological Magnetic Transitions in NdCo5 Rare‐Earth Magnets

Abstract: Particle‐like magnetic textures with nanometric sizes, such as skyrmions, are potentially suitable for designing high‐efficiency information bits in future spintronics devices. In general, the Dzyaloshinskii–Moriya interactions and dipolar interactions are the dominant factors for generating nonlinear spin configurations. However, to stabilize the topological skyrmions, an external magnetic field is usually required. In this study, the spontaneous emergence of skyrmions is directly observed, together with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…The Curie temperature ( T c ) of FGT in this work was determined to be about 270 K through the magnetization derivative as a function of temperature (see Figure S1 in the Supporting Information). Moreover, it has been found that the magnetocrystalline anisotropy changes with temperature in many uniaxial magnets, such as Fe 3 Sn 2 and NdCo 5 and even the Fe n GeTe 2 systems that have been widely investigated recently, which could induce a spin reorientation transition (SRT) that promises the emergence of noncollinear magnetic textures. Hence, to reveal the magnetic properties of FGT further, M–H curves were measured at different temperatures with a magnetic field parallel to the c axis and ab plane (see Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The Curie temperature ( T c ) of FGT in this work was determined to be about 270 K through the magnetization derivative as a function of temperature (see Figure S1 in the Supporting Information). Moreover, it has been found that the magnetocrystalline anisotropy changes with temperature in many uniaxial magnets, such as Fe 3 Sn 2 and NdCo 5 and even the Fe n GeTe 2 systems that have been widely investigated recently, which could induce a spin reorientation transition (SRT) that promises the emergence of noncollinear magnetic textures. Hence, to reveal the magnetic properties of FGT further, M–H curves were measured at different temperatures with a magnetic field parallel to the c axis and ab plane (see Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, spontaneous biskyrmions could exist at a higher temperature (>300 K) including room temperature in the heating process. Although the domain evolution between biskyrmions and EIPDs looks similar in Nd 2 Co 17 and NdCo 5 , the relatively strong easy-plane anisotropy in the soft magnet Nd 2 Co 17 indicates significantly different biskyrmion origination in contrast to those in NdCo 5 determined by the uniaxial anisotropy near T c …”
mentioning
confidence: 86%
“…The existence of skyrmions at room temperature and zero field, i.e., spontaneous skyrmions at room temperature, is highly anticipated for spintronic applications. However, despite the theoretically proposed spontaneous ground state, the experimental discovery is very limited , especially at room temperature and in materials with easy-plane magnetic anisotropy.…”
mentioning
confidence: 99%
“…[56] Furthermore, the topology of the "Yin-Yang" symbol in the green box remains controversial. [57] Some research proposed that it was a biskyrmion, [58][59][60] whereas recent reports claimed that it was a modified trivial bubble. [21,61] Further detailed analysis of this spin texture is beyond the scope of this study.…”
Section: M(h) Curves In Figurementioning
confidence: 99%